Emotional intelligence approach as a predictor of job satisfaction among midwives in Northern Iran: A descriptive-correlational study - Fatemeh Zolfaghary; Hajar Pasha; Fatemeh Bakouei; Reza MashaghiTabari; Hajar Adib-Rad (Journal of Education and Health Promotion)
BACKGROUND: Emotional intelligence (EI) is an important skill for midwives. Our study aimed to understand EI as a predictor of job satisfaction among midwives. MATERIALS AND METHODS: This descriptive-correlational study was conducted on 143 employed midwives in maternity wards of government and private hospitals, as well as healthcare centers in Iran. The data were collected using demographic fertility characteristics, EI, and job satisfaction questionnaires. For the assessment of EI, Bar-On’s Emotional Intelligence questionnaire was used which consists of 90 items. For the assessment of job satisfaction, Herzberg’s Job Satisfaction Questionnaire was used, which consists of 72 items. The significance level of the tests was considered to be P < 0.05. RESULTS: The results of the study showed that the mean EI and job satisfaction of midwives were moderate (316.57 ± 33.64 and 278.58 ± 25.95, respectively). According to Pearson correlation coefficients, there was a significant positive correlation between total job satisfaction and total EI scores (r = 0.356, P = 0.0001). According to the results of multiple linear regression analysis after adjusting for other variables, job satisfaction of midwives had a significant positive association with total EI and friendly relationships with supervisors (β = 0.258, P = 0.022 and β = 0.267, P = 0.046, respectively). CONCLUSION: This study showed that high EI enhances midwives’ job satisfaction. Therefore, midwifery managers should create conditions that help enhance the EI and satisfaction of midwives.